Henry Eld papers - Eld, Henry, 1814-1850.
Volume (circa 150 items) containing letters from Eld to his father and other family members describing his activities while serving on the U.S.S. Delaware in the Mediterranean; on the U.S.S. Peacock and U.S.S. Vincennes while visiting South America, the South Pacific, and the northwest coast of the U.S., as a member of the U.S. Exploring Expedition led by Charles Wilkes; on the U.S.S. Flirt, U.S.S. John Adams, and the U.S.S. North Carolina; in Washington, D.C., where he helped in the preparation of Wilkes' narrative of the expedition; and on the U.S.S. Ohio during the War with Mexico in the siege of Vera Cruz, and later, when he escorted the American minister to Brazil and joined the Pacific Squadron. Topics include naval matters, places of interest, family affairs, and speculative ventures in Lake Superior mining and in California land.
Microfilm edition available
Microfilm produced from originals in the Manuscript Division.
Naval officer.
Collection material in English.
Keywords: Wilkes, Charles, -- 1798-1877.; United States. -- Navy -- History; Delaware (Ship); Flirt (Schooner); John Adams (Ship); North Carolina (Ship of the line); Ohio (Ship of the line); Peacock (Ship); Vincennes (Sloop of war); Land speculation -- California; Mexican War, 1846-1848.; Mines and mineral resources -- Superior, Lake; Voyages and travels; Mediterranean Region -- Description and travel; Northwest, Pacific -- Description and travel; Oceania -- Description and travel; South America -- Description and travel; Naval officers